Near Real-Time 3D Path Visualization for Navigation Systems with IMU Sensor and Kalman Filter - Paneru, Biplov (Journal of Ubiquitous Computing and Communication Technologies, 2023)
Path tracing or simulation in robotics Operating System ROS is very popular in highly dynamic research projects. The Matplotlib’s 3D path tracing is a graphical 3-axis plotting tool with real- time data visualization over a very long range. The data’s are generated in all 3 dimensions from accelerometer readings for visualizing the ground station navigation system. The communication between the two radio modules are established and the data’s are transmitted between the two modules that are placed remotely. The data can be plotted in real-time in 3 Dimensions and then, visualized. The main goal of path tracing is to make a comparative study between 3 axis displacement as any kind of irregular plot or trace can be a sign of a dangerous situations that can occur. There are many other significances of this concept that can be used in navigation systems.